Natural products and dietary interventions on liver enzymes: an umbrella review and evidence map - Li, Zhongyu; Wu, Jiao; Zhao, Yingpan; Song, Jinjie; Wen, Yandong (Frontiers in Nutrition, 2024)
Background: The association between natural products and dietary interventions on liver enzymes is unclear; therefore, this study aimed to examine the evidence for thetheir effects of natural products and dietary interventions on liver enzymes in adults. Methods: PubMed, Embase, and Cochrane Library of Systematic Reviews databases were searched from inception until till March 2023. The Assessment of Multiple Systematic Reviews-2 (AMSTAR-2) and Grading of Recommendations Assessment, Development, and Evaluation (GRADE) systems were used to assess the methodological and evidence quality, and the therapeutic effects were summarized in a narrative form. Results: A total of 40 meta-analyses on natural products (n=25), dietary supplements (n=10), and dietary patterns (n=5) were evaluated, and results were presented in a narrative form. The overall methodological quality of the included studies was relatively poor. The results indicated that positive effects were observed for nigella sativa, garlic, artichoke, curcumin, silymarin, vitamin E, vitamin D, L-carnitine, propolis, and polyunsaturated fatty acids on certain liver enzymes. The dietary patterns, including high-protein, Mediterranean, and calorie-restriction diets and evening snacks, may reduce liver enzymes; however, other supplements and herbs did not reduce liver enzyme levels or have minimal effects. The evidence quality was generally weak given the risk of bias, heterogeneity, and imprecision. Conclusion: This umbrella review suggests that natural products and dietary interventions have beneficial therapeutic effects for on liver enzymes levels. In additionFurther, further clinical trials are necessary to establish the effectiveness of supplements that reduce liver enzymes.